2015
DOI: 10.1590/1678-4499.0147
|View full text |Cite
|
Sign up to set email alerts
|

Competitividade relativa de cultivares de arroz irrigado com Aeschynomene denticulata

Abstract: This study evaluated the relative competitive ability of rice cultivars in the presence of a joint-vetch (Aeschynomene denticulata) biotype, at different replacement levels of plants in the association. The experiments were conducted in a randomized complete block design with four replications. First, it was determined the population of plants in which the final dry mass remains constant, both for the rice and for the joint-vetch (24 plants per pot). Later, two experiments were carried out to evaluate the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 24 publications
7
16
2
5
Order By: Relevance
“…It is noteworthy that, in substitutive experiments, there is little evidence of having qualitative changes due to population increase, i.e., the dominance of one species over another rarely changes with the change of the population (Cousens & O'Neill, 1993). The results observed in this study are corroborated by the ones verified by Agostinetto et al (2008), Fleck et al (2008), Agostinetto et al (2009) and Galon et al (2011Galon et al ( , 2015. However, conflicting results have been verified by Agostinetto et al (2013), who found different behavior when rice and soybeans competed with cockspur, and the crops, in this case, were more competitive than the weeds, therefore occurring differences between species in competition.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…It is noteworthy that, in substitutive experiments, there is little evidence of having qualitative changes due to population increase, i.e., the dominance of one species over another rarely changes with the change of the population (Cousens & O'Neill, 1993). The results observed in this study are corroborated by the ones verified by Agostinetto et al (2008), Fleck et al (2008), Agostinetto et al (2009) and Galon et al (2011Galon et al ( , 2015. However, conflicting results have been verified by Agostinetto et al (2013), who found different behavior when rice and soybeans competed with cockspur, and the crops, in this case, were more competitive than the weeds, therefore occurring differences between species in competition.…”
Section: Resultssupporting
confidence: 87%
“…Similar results occurred when wheat grew with ryegrass (Rigoli et al, 2008); barley, when infested by ryegrass (Galon et al, 2011); and rice, in the presence of Aeschynomene denticulata (common names vary regionally) (Galon et al, 2015).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations